Consider the Physical Education of our Young People, It is Important to Educate Them to Be Physically Endurant for the Military Service - Ubaydullaev Saidakbar Saydalievich (Periodica Journal, 2023)
In the article, tips are given to increase the methods of training in the spirit of physical education and endurance. It shows how these types of education can benefit the youth themselves, social life and humanity. At the same time, the article presents activities that affect the physical condition and personal characteristics of young people, increase their health and abilities. Such types of education are very important for the life of young people, because they should improve their health and the ability to think independently.
Keywords: thinking; physical education